Factors associated with sarcopenia in subjects aged 80 years and over - Santos, Vanessa Ribeiro dos [UNESP]; Destro Christofaro, Diego Giulliano [UNESP]; Gomes, Igor Conterato; Agostinete, Ricardo Ribeiro [UNESP]; Freitas Junior, Ismael Forte [UNESP]; Gobbo, Luis Alberto [UNESP] (Pontificia Universidade Catolica Campinas, 2015)
ObjectiveTo analyze whether sarcopenia is associated with sociodemographic factors and chronic noncommunicable diseases in adults aged 80 years and older.MethodsThe sample consisted of 120 adults aged 80 to 95 years (83.4 +/- 2.9 years) from the city of Presidente Prudente (Sao Paulo, Brazil), of which 76 were females (83.4 +/- 3.0 years) and 44 were males (83.4 +/- 2.6 years). The study sociodemographic and epidemiological factors were: age stratum, gender, marital status, education level, chronic noncommunicable diseases, ethnicity, and nutritional status. Body composition was determined by Dual-Energy X-Ray Absorptiometry and sarcopenia was identified by the appendicular lean mass ratio (upper limb lean mass + lower limb lean mass [kg]/height [m](2)). The Chi-square test analyzed whether sarcopenia was associated with sociodemographic and epidemiological factors and binary logistic regression expressed the magnitude of the associations. The data were treated by the software Statistical Package for the Social Sciences (17.0) at a significance level of 5%.ResultsThe factors associated with sarcopenia were gender, age, nutritional status, and osteopenia/osteoporosis.ConclusionThe factors gender, age, nutritional status, and osteopenia/osteoporosis are independently associated with sarcopenia in adults aged 80 years and older.

OBJETIVO: Analisar a associação entre sarcopenia, fatores sociodemográficos e doenças crônicas não transmissíveis em idosos longevos. MÉTODOS: A amostra foi constituída por 120 idosos - 76 mulheres (83,4±3,0 anos) e 44 homens (83,4±2,6 anos) -, com idade entre 80 e 95 anos (83,4±2,9 anos), residentes na cidade de Presidente Prudente (SP), Brasil. Os fatores sociodemográficos e epidemiológicos investigados foram: estrato etário, sexo, estado civil, escolaridade, doenças crônicas não transmissíveis, etnia e estado nutricional. A análise da composição corporal foi feita pela técnica de absorptiometria de raios-X de dupla energia, e, para identificação da sarcopenia, foi utilizada a razão da massa apendicular (massa magra dos membros superiores mais massa magra dos membros inferiores [kg]/estatura [m]2). Para tratamento estatístico, foi empregado o teste Qui-quadrado para analisar a associação entre os fatores sociodemográficos, epidemiológicos e sarcopenia, e a análise de regressão logística binária foi utilizada para expressar a magnitude das associações. Foi utilizado o software Statistical Package for the Social Sciences (17.0), e o nível de significância estabelecido foi de 5%. RESULTADOS: Os fatores que se associaram com a sarcopenia foram: sexo, idade, estado nutricional, osteopenia/osteoporose. CONCLUSÃO: O sexo, a idade, o estado nutricional e a presença de osteopenia/osteoporose são fatores que estão independentemente associados à sarcopenia em idosos longevos.
Fatores associados à sarcopenia em idosos longevos
Keywords: Chronic diseases; Aged, 80 and over; Demographic indicators; Sarcopenia; Doenças crônicas; Idosos 80 anos ou mais; Indicadores demográficos; Sarcopenia